Smart Dust Detection and Automation Cleaning of Photovoltaics Panel - Mohamad Rafie, Muhammad Aiman; Sy Ki, Sim (Evolution in Electrical and Electronic Engineering, 2023)
The efficient operation of photovoltaic (PV) systems heavily relies on the cleanliness of their solar panels. Dust accumulation on PV panels can significantly reduce their power output and overall performance. The purpose of smart dust detection and automated cleaning of PV systems is to optimize their energy generation and maintenance. The system utilizes an array of low-cost dust sensors strategically placed across the PV panel array. These sensors continuously monitor the dust accumulation levels on individual panels and wirelessly transmit the data to a central control unit. The control unit employs advanced algorithms to analyze the sensor data and determine the optimal cleaning schedule based on predefined cleanliness thresholds. Upon detecting a significant dust accumulation on a particular panel, the control unit triggers the automation cleaning mechanism. The cleaning mechanism consists of an ESP32, two DC motors, a water pump, a relay, and a motor driver (L298N). The results demonstrated a significant improvement in the voltage output of the PV system after implementing the smart dust detection and automation cleaning approach. The system effectively reduced energy losses due to dust accumulation while minimizing manual intervention and maintenance costs. In conclusion, smart dust detection and automation cleaning systems offer an innovative solution for enhancing the efficiency and performance of PV systems. By automating the cleaning process based on real-time dust detection, the system optimizes energy generation and reduces the need for manual maintenance. This approach contributes to the sustainability and longevity of photovoltaic installations, enabling them to operate at their maximum potential while minimizing downtime and associated costs.